A recommended closed-loop assessment of learning outcomes process for hospitality programs: The experience of two programs, Part 1. Issue 1 (1st July 2019) - Reich, Allen Z.; Collins, Galen R.; DeFranco, Agnes L.; Pieper, Suzanne L.
Abstract : Purpose: Because of the increasingly higher expectations of accrediting organizations, calls for greater accountability from state governments, and students' demand for an education that prepares them for a career, most hospitality programs are now required to have an effective assessment of learning outcomes process. The increasing popularity of the assessment of learning outcomes process is viewed as highly positive because it can be considered as best practices in higher education. The paper aims to discuss this issue. Design/methodology/approach: This is Part 1 of a two-part article that provides an overview of the justifications for implementing an assessment of learning outcomes process, the steps that were developed by two hospitality programs and the experiences of the two programs during implementation of the seven steps. Part 1 includes foundational principles of the process and the first three of the seven steps. Findings: The steps in a closed-loop assessment of learning outcomes process are relatively detailed; however, because of changes in expectations of stakeholders and the requirements of accreditors, they are now mandatory for most hospitality programs. Therefore, the choice is not whether to implement them, but when to implement them. From a competitive standpoint, it is to the program's advantage to begin as soon as possible. Another factor to consider is that the implementation of an effective closed-loop assessment of learning outcomes process will take several years to complete. Originality/value: This paper is presenting a critical view of one of, if not the most important concepts in higher education, the closed-loop assessment of learning outcomes process. Hopefully, the information on the process that is provided and the experiences of the two programs can shorten the learning curve for other hospitality programs.